A new technique of completely diverted tube ileostomy for the protection of colorectal anastomosis: a pilot study - YEGEN, ŞEVKET CUMHUR; UPRAK, TEVFİK KIVILCIM (WILEY, 2020)
Aim This study was designed to evaluate a new technique for a completely diverting tube ileostomy achieved through temporary occlusion of the distal ileum using a flexible rubber strip. Methods This prospective interventional study was conducted in one centre. Patients who underwent colorectal resections with a primary anastomosis and who were deemed as requiring a defunctioning stoma were included in the study. After completion of resection and anastomosis, the tube ileostomy was fashioned by inserting a reinforced (spiral) endotracheal tube with an inner diameter of 7.5 mm into the ileum. To provide complete faecal diversion, temporary occlusion of the distal ileum was performed using a flexible rubber strip. The primary outcome of this study was the incidence of complete diversion achieved using this method. Results Fifty consecutive patients underwent a diverted tube ileostomy using the technique described above. Defaecation before removal of the strip did not occur in any of the patients inferring that complete diversion was observed in all patients (100%). The tube was removed at postoperative week 3. After tube removal, the resulting enterocutaneous fistulas closed spontaneously in a median of 6 (2-30) days. Conclusion The diverting tube ileostomy technique using an easily removable rubber strip to defunction the colorectal anastomosis is a safe and effective method that precludes the need to fashion a stoma.
Keywords: tube ileostomy; colorectal anastomosis; complete faecal diversion; LOW ANTERIOR RESECTION; LOOP ILEOSTOMY; DEFUNCTIONING STOMA; FECAL DIVERSION; CLOSURE; MORBIDITY